The Consultants’ Roles And Functions In Design And Build Method - Tan, Chiang Hwang (Universiti Sains Malaysia, 2005)
Consultants are the specialist that offered services in their area of specialisation in building construction. They can be any independent designer, advisor or quantity surveyor employed neither by the contractor nor the employer. In design and build method, the roles and the position of the consultants are quite different from the traditional method where they have the contractual relationship with the contractor but not the employer.